Relationship Between Exposure Levels of Dust Polymethyl Methacrylate And Characteristics of Workers With Subjective Respiratory Complaints in Dental Engineering Laboratory, Dki Jakarta Region in 2021 - Tarsilah Sila Tarsilah; Endang Prawesthi; Rosita Gusfourni (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2022)
The manufacture of dentures, especially from polymethyl methacrylate affects the health of workers, especially those related to breathing. The manufacture produces dust of various sizes. The effects of exposure to dust cause discomfort at work and have a negative impact on health. This research objective was to determine the relationship between exposure to polymethyl methacrylate and subjective respiratory complaints. The method used was analytical quantitative research with a cross-sectional with a sample of 5 objects and a sample of 30 workers.dust content polymethyl methacrylate with a Portable High Volume Air Sampler and measurement of subjective respiratory Complaints with a questionnaire. There is a relationship between exposure to dust levels of polymethyl methacrylate on subjective respiratory complaints with p value = 0.006. The dust content of polymethyl methacrylate exceeds the threshold value at 2 sites (40% of the samples). There is a relationship between exposure to dust levels of polymethyl methacrylate on subjective respiratory complaints, p value 0.006 (p <0.05).